Anpassad E-handel : Design för en förändrad målgrupp - Johansson, Frans (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2021)
In 2020, the common man was exposed to a large number of changes to his everyday life, in connection with the outbreak of the pandemic disease Covid-19. These changes left many questions as to how everyday life should be handled, including where and how a person should shop. In connection with the restrictions introduced, the e-commerce market saw a noticeable increase in consumption, where people who had not shopped before started during the pandemic. However, this increase leaves the question, are all the needs of the new target group for e-commerce met? Around this question, this project was created, as a ten-week degree project in Industrial Design Engineer with a Bachelor’s degree. The project was carried out at Luleå University of Technology during the spring of 2021. The purpose and goal of the project was to investigate the change in the target group for e-commerce, as well as its needs. Based on the needs of the new target group, a concept will be developed that tries to address these needs. This in an attempt to create a trading environment that does not feel stressful or frightening for consumers. The project used IDEO’s Human centered design process, which took inspiration from the target group in the form of surveys, target group interviews and concept selection methods. The end result of the project was a concept on three pages of a clothing store’s website. The three pages were the start page, the category page and the product page. These three were based on the needs of the users, which emerged during the project. The results were developed using relevant theory and user-centered design methods. Under 2020 utsattes den gemena människan för en stor mängd förändringar till dess vardag, i samband med utbrottet av pandemisjukdomen Covid-19. Dessa förändringar lämnade många frågetecken till hur vardagen skulle hanteras, bland annat hur man som person borde handla. I samband med införda restriktioner såg e-handelsmarknaden en märkbar ökning av konsumtion, där personer som inte hade handlat innan ...